Genetic variants associated with methotrexate-induced mucositis in cancer treatment: A systematic review and meta-analysis. (May 2021) - Maagdenberg, Hedy; Oosterom, Natanja; Zanen, Jolanda; Gemmati, Donato; Windsor, Rachael E.; Heil, Sandra G.; Esperón, Patricia; Jabeen, Shakila; Ruiz-Argüelles, Guillermo J.; Zolk, Oliver; Hoerning, Susanne; Sleurs, Charlotte; et al.
Graphical abstract: Highlights: 57 studies were included in this systematic review; 26 in the meta-analysis. A total of 34 SNPs were associated with (more severe) mucositis in ≥1 study. MTHFRc.677C > T was associated with more severe mucositis (OR 2.53, 95 %CI 1.48–4.32). MTRRc.66A > G was associated with mucositis (OR 2.08, 95 %CI 1.16–3.73). Current studies are heterogeneous in design with different case-control definitions. Abstract: Methotrexate (MTX), an important chemotherapeutic agent, is often accompanied with mucositis. The occurrence and severity are unpredictable and show large interindividual variability. In this study, we review and meta-analyze previously studied genetic variants in relation to MTX-induced mucositis. We conducted a systematic search in Medline and Embase. We included genetic association studies of MTX-induced mucositis in cancer patients. A meta-analysis was conducted for single nucleotide polymorphisms (SNPs) for which at least two studies found a statistically significant association. A total of 34 SNPs were associated with mucositis in at least one study of the 57 included studies. Two of the seven SNPs included in our meta-analysis were statistically significantly associated with mucositis: MTHFR c.677C > T (recessive, grade ≥3 vs grade 0–2, OR 2.53, 95 %CI [1.48–4.32], False Discovery Rate[FDR]-corrected p-value 0.011) and MTRR c.66A > G (overdominant, grade ≥1 vs grade 0, OR 2.08, 95 %CI [1.16–3.73], FDR-corrected p-value 0.042).